Simulation of broadcasting method based on busy tone - Sheng-hong XU; Qing-tian HAN; Wen-jing CAO (Tongxin xuebao)
In ad hoc network with high dynamic topology,broadcasting method based on handshake mechanism was not efficient.Therefore,a broadcasting method based on busy tone was proposed.This method was modeled and implemented with the network simulation platform OPNET,and the performance of the broadcasting method was analyzed based on experimental results.Experimental results show that,the broadcasting method based on busy tone is applicable to the network with high dynamic topology.